Serious Attention of Health Information Seeking Behavior in Covid-19 Pandemic - Meisam Dastani; Alireza Atarodi (Mashhad University of Medical Sciences, 2020)
Covid 19 viral disease (Coronavirus 2019) was created in December 2019 in Wuhan of China and it quickly spread worldwide and it is a serious issue for public sanitation and people health and all the societies on the planet. As other pandemic diseases, people want to know what can be done to prevent and treat the disease. Considering that no specific controls or any methods have yet been developed to prevent and treat the disease, the need for taking care of themselves and to prevent the prevalence of this disease is significant as well. People in affected communities should learn to protect themselves from the potential dangers and harms of the spread of this mysterious and novelty virus. Having information is the first step to achieve health and health information is as a relationship between health education and health promotion. So access to health information helps to learn more about health and choosing a healthy lifestyle. Health information covers a wide range of information that includes information about diseases, how to prevent and treat them which is one of the main concerns of most people. Health information seeking behavior is widely regarded as a way for people to gain information about health, illness, health promotion and health risks. Currently lots of information about the spread of Covid-19 is being spread though new web media such as websites and social networks.